INTEGRATED REMOTE SENSING AND GIS TECHNIQUES FOR GROUNDWATER EXPLORATION IN SEMI-ARID REGION: A Case of Karamoja Region €“ Uganda - Lubang, B; Nobert, J.; Mtalo, E G (Tanzania Journal of Engineering and Technology, 2018)
Groundwater is a precious resource that covers wide geographical extent. Proper evaluation is required in order to ensure prudent use of groundwater resources. The current groundwater assessment in Karamoja region, as in many parts of the world, uses Apparent Resistivity and Vertical Electrical Sounding, which has limited coverage to some localized usually predetermined areas. Comprehensive groundwater development program needs a wide area coverage and large volume of multidisciplinary data. In the present study, an integrated remote sensing and GIS based methodology is developed and tested for the evaluation of groundwater resources of Karamoja Sub Region, Northeastern Uganda. The components of the study are delineation of the groundwater potential zones in the area and evaluation of the relationship between delineated groundwater potential zones and aquifer characteristics. The groundwater potential zones are determined by the relevant layers, which include hydro- geomorphology, lineament density, slope, drainage density, overburden thickness and aquifer depth, rainfall, geology, land use, and soil were integrated in Arc/Info grid environment. Weighted index overlay method developed by Multi Criteria Analysis (Analytical Hierarchy Process) was used to assign weights to the different map layers. All the information layers were been integrated through GIS analysis, employing the use of Natural Break (Jenks) method for classification. Alexandru groundwater potential zoning using the Transmissivity values was used for the final classification of the potential zones and correlation with ground-truth data. Over 70% correlation was achieved showing the significance of GIS in groundwater mapping.